Rola informacji w podejmowaniu decyzji marketingowych w joint venture na rynku polskim - Oczkowska, Renata (Role of Information in Taking Marketing Decisions in Joint Ventures on Polish Market, 2006)
In the text there are presented the results of research on evaluation of the information resources in possession of companies, conducted in 148 joint venture enterprises in Poland. The evaluation was made in accordance with different marketing problems. Owing to the analysis presented in the article we can state that the best evaluated information resources include the data that allow extended estimation of company's own market position, market growth tendencies and consumers' needs and preferences. With the results received there may be a conclusion made that joint ventures plan the activities that are based on appropriately defined marketing concept.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1107, s. 387-391